Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd006047.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Household interventions for preventing domestic lead exposure in children

Abstract: Analysis 2.6. Comparison 2 Environmental -Dust control, Outcome 6 Blood lead level (dichotomous ≥15 µg/dL). . Analysis 2.7. Comparison 2 Environmental -Dust control, Outcome 7 Blood lead level (dichotomous ≥15 µg/dL) ICC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…A 2012 review of 14 studies found that educational and home-based dust control interventions are not effective in reducing blood lead levels of young children (44). In Mount Isa, education campaigns may have increased public awareness; however, there is insufficient evidence to conclude that lead levels in children have decreased and the latest results suggests that ~50% of Mount Isa children have a blood lead above 5 μg/dL, the proposed new intervention in Queensland (21).…”
Section: Assessment Of Current Interventions and Leadershipmentioning
confidence: 99%
“…A 2012 review of 14 studies found that educational and home-based dust control interventions are not effective in reducing blood lead levels of young children (44). In Mount Isa, education campaigns may have increased public awareness; however, there is insufficient evidence to conclude that lead levels in children have decreased and the latest results suggests that ~50% of Mount Isa children have a blood lead above 5 μg/dL, the proposed new intervention in Queensland (21).…”
Section: Assessment Of Current Interventions and Leadershipmentioning
confidence: 99%
“…Increased risk of lead exposure is determined by exposure during pregnancy (lead crosses the placenta) [86,87], increased intake of food, water and air relative to body weight, risk behaviour (for example, hand-to-mouth behaviour), and more time spent in polluted environments (for example, home) [1,37,88,89]. The absorption of lead is four to five times higher in children than in adults (excluding pregnant women), and only 30% of the absorbed lead is excreted, while 70% is accumulated in bone, blood, brain, kidneys, liver and lungs [45].…”
Section: Introductionmentioning
confidence: 99%
“…Despite sharp reductions in the general population’s exposure to lead since the 1970s, substantial numbers of ethnic minority and low-income children continue to exhibit unacceptably high BLLs [101,102]. To our knowledge, no systematic review has been undertaken to assess the effectiveness of interventions to reduce lead in consumer products and drinking water, although a systematic review has been conducted for household interventions for preventing domestic lead exposure in children [89]. This review is undertaken in the course of the development of WHO guidelines for the prevention and management of lead poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…7 Unfortunately, studies that evaluated the efficacy of parent education or provision of cleaning equipment to families failed to show significant reductions in children's blood lead concentrations. 8 Similarly, calcium and iron supplementation have not consistently been shown to be efficacious in reducing blood lead concentrations of children. 9,10 Collectively, these studies indicate that the focus of prevention should be on reducing the sources of childhood lead exposures rather than identifying children who have already been unduly exposed or attempting to ameliorate the toxic effects of lead exposure.…”
Section: Scope Of the Problemmentioning
confidence: 99%